Is ambiguity tolerance malleable? Experimental evidence with potential implications for future research - Endres, Megan L.; Camp, Richaurd; Milner, Morgan (Frontiers in Psychology, 2015)
We conducted two research studies to address the malleability of TA by manipulating situational ambiguity. Students participated in a semester-end assessment of their management skills (n = 306). In Study 1, students in low and moderate ambiguity conditions had significantly higher post-experiment TA, more positive change in self-efficacy, and marginally higher faculty ratings. In Study 2, a control group (n = 103) did not participate in the assessment and was established for comparison to the first study results. The Study 2 students reported TA significantly lower than Study 1 students in the low and moderate ambiguity conditions. The control group TA was not significantly different from that of the Study 1 high ambiguity condition. This further suggested TA’s situational malleability, as those who had controlled access to structured information appeared to have increased their TA over that observed in the other two groups. These results suggest that TA may be malleable. We review the relevant literature, offer hypotheses, report our analyses and findings, and then propose future research and potential prescriptive applications in such areas as management development, assessment, and decision-making.